"LUDRUK SIAGA BENCANA" LUDRUK AS A STORYTELLING EDUCATION FOR FLOOD DISASTER PREPAREDNESS AT SDN BLEGA 1 - -, Mufarika; Mayasari, Mulia; Handayani, Nor Indah; Safitri, Safitri; Nugroho, Dimas Eko (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Indonesia is a country that is prone to disasters. There are many impacts of disasters that can occur, starting from damage to buildings, houses, basic service facilities, schools and also health. Apart from that, it also causes casualties in various age groups. The low level of knowledge and community preparedness, especially the children's age group, is one of the things that needs attention. Children as a group vulnerable to disasters need to be given socialization in the form of education about flood disasters that generally occur. The aim of this activity is to increase students' knowledge, understanding and preparedness for disasters, especially floods. The activity method is carried out face to face using the Madurese ludruk method, an art of speaking using Madurese language packaged in the form of an arts drama. The activity was carried out at SDN Blega 1 with a total of 15 cadre participants. And a total of 75 students. The activity stages start from preparation, implementation, evaluation, and end with the preparation of reports and publication of activity results. Participants were also given a questionnaire to assess knowledge about flood disasters. The research method used is descriptive with the researcher acting as an observer. Documentation, observation and test methods are used to collect data. The results obtained show that Ludruk's "LUDRUK SIAGA BENCANA" method as flood preparedness education at SDN Blega 1 can be used to develop students' knowledge, flood management and cultural skills.